Conformation and microenvironment of the active site of a low molecular weight 1,4-beta-D-glucan glucanohydrolase from an alkalothermophilic thermomonospora sp.: involvement of lysine and cysteine residues - Jagtap, Sharmili; Rao, Mala (Biochemical and Biophysical Research Communications, 2006)
Conformation and microenvironment at the active site of 1,4-beta-D-glucan glucanohydrolase was probed with fluorescent chemo-affinity labeling using o-phthalaldehyde. OPTA has been known to form a fluorescent isoindole derivative by cross-linking the proximal thiol and amino groups of cysteine and lysine. Modification of lysine of the enzyme by TNBS and of cysteine residue by PHMB abolished the ability of the enzyme to form an isoindole derivative with OPTA. Kinetic analysis of the TNBS and PHMB-modified enzyme suggested the presence of essential lysine and cysteine residues, respectively, at the active site of the enzyme. The substrate protection of the enzyme with carboxymethylcellulose (CMC) confirmed the involvement of lysine and cysteine residues in the active site of the enzyme. Multiple sequence alignment of peptides obtained by tryptic digestion of the enzyme showed cysteine is one of the conserved amino acids corroborating the chemical modification studies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: 1; 4-beta-D-glucan glucanohydrolase; active site microenvironment; Cysteine; lysine; OPTA; PHMB; Thermomonospora sp.; TNBS

Crystallization and preliminary X-ray characterization of a thermostable low-molecular-weight 1,4-beta-D-glucan glucohydrolase from an alkalothermophilic thermomonospora sp. - Manikandan, K.; Jagtap, Sharmili; Rao, M.; Ramakumar, S. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2006)
{Cellulases catalyze the hydrolysis of beta-1,4-glycosidic linkages within cellulose, the most abundant organic polymer on earth. The cellulase (TSC; EC 3.2.1.4) from an alkalothermophilic Thermomonospora sp. has a low molecular weight of 14.2 kDa. It is optimally active at 323 K and stable over the wide pH range of 5 - 9. Moreover, it has bifunctional activity against cellulose and xylan polymers. In this study, TSC was purified from the native source and crystallized by the hanging-drop vapour-diffusion method. The crystals belong to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 49.9

Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel